"Nanoscale Lattice Fence" in a Metal-Organic Framework: Interplay between Hinged Topology and Highly Anisotropic Thermal Response. - DeVries, Lucas D.; Barron, Paul M.; Hurley, Evan P.; Chunhua Hu; Wonyoung Choe (Journal of the American Chemical Society, 2011)
A thermoresponsive, 3D hinged metal-organic framework (HMOF-1) assembled from meso-tetra(4-pyridyl)porphine and CdI exhibits a 3D "lattice fence" topology with extraordinary thermal expansion and shrinkage. A simple structural model is established to elucidate such a drastic thermal response. The hinged structure model presented here can also be applied to other "lattice fence" topologies with little or no modification, depending on the symmetry of the molecular building blocks.